Syrian Arab Republic : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Syrian Arab Republic. (IMF Staff Country Reports; Country Report ;, 2009)
The staff report for the 2008 Article IV Consultation of the Syrian Arab Republic on economic developments and policies is discussed. The impact of adverse global and regional developments currently under way on the Syrian economy is expected to be relatively moderate in the short term. The effects are likely to be through weakening FDI, remittances, and demand for Syrian exports from the Gulf region. The positive outlook is contingent on perseverance in advancing fiscal and structural reforms and an improvement in global conditions over the medium term.